AB0196 THE ASSOCIATION BETWEEN OSTEOPOROSIS AND FUNCTIONAL IMPAIRMENT EVALUATED BY THE LOCOMO25 IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Kashiwagura, T.; Kobayashi, M.; Sugimura, Y.; Kawano, T.; Sato, H.; Shimada, Y.
Abstract : Background: Locomotive syndrome is a condition in which activities of daily living are affected by impairment of the motor organs, most often due to rheumatoid arthritis (RA). Locomo25 is a new index developed for the early detection of locomotive syndrome. It consists of 25 items associated with pain, physical activity, and subjective state of health, with a score of 7 points or higher classed as Grade 1 locomotive syndrome and a score of 16 points or higher as Grade 2. In RA, joint impairment causes the appearance of problems affecting motor organs as a whole, as well as progressive functional impairment. As functional impairment progresses, it causes increasing immobility, which raises the risk of osteoporosis. Objectives: Locomo25 was used to investigate functional impairment and its association with RA disease activity and osteoporosis indicators. Methods: The subjects were 105 patients with RA (24 men and 81 women) with a mean age of 68.7 (28–91) years. In terms of staging, 25 were Stage I, 22 Stage II, 17 Stage III, and 41 Stage IV, and their motor disability was Steinbrocker Class 1 in 68 cases, Class 2 in 27, Class 3 in 9, and Class 4 in 1. Disease activity according to the Disease Activity Score 28 with erythrocyte sedimentation rate (DAS28 ESR) was assessed as remission in 44 cases, low disease activity in 24, moderate in 33, and high in 4. The associations between the Locomo25 score and disease activity indices, bone mineral density (BMD), and bone turnover markers (TRACP-5b, NTX, urinary DPD, BAP, total P1NP, and 25(OH)D) were investigated. Results: Locomo25 grade was 0 in 37 cases (35.2%), 1 in 24 (22.9%), and 2 in 44 (41.9%). Locomo25 grade was significantly associated with Steinbrocker class ( r = 0.4299, Spearman's rank correlation coefficient, p < 0.0001). DAS28 ESR and Health Assessment Questionnaire scores increased as locomotive syndrome progressed. There was no significant difference in eGFR between groups, but bone resorption markers (TRACP-5b, NTX, and urinary DPD) and a bone quality marker (pentosidine) decreased significantly as locomotive syndrome progressed. There were no significant differences in BMD or other bone turnover markers. Conclusion: The Locomo25 score was useful for evaluating functional impairment in RA. The prevalence of Grade 2 locomotive syndrome in the general population is reported to be around 25%, and many patients with RA had advanced locomotive syndrome. Although there was no significant difference in BMD, elevated bone resorption and deteriorating bone quality were associated with progressive functional impairment, suggesting that RA patients with advanced locomotive syndrome may be at risk of increasingly severe osteoporosis as a result of immobility. References: [1]Yoshimura Y, Ishijima M, Ishibashi M, Liu L, Arikawa-Hirasawa E, Machida S, Naito H, Hamada C, Kominami E. J Orthop Sci. 2019 Nov;24(6):1094-1104. doi: 10.1016/j.jos.2019.08.009. Epub 2019 Sep 3. [2]Siu PPY, Cheung PWH, Cheung JPY. J Orthop Sci. 2019 Nov;24(6):1110-1117. doi: 10.1016/j.jos.2019.07.012. Epub 2019 Aug 14. Disclosure of Interests: None declared